Low oxygen levels with high redox heterogeneity in the late Ediacaran shallow ocean: Constraints from I/(Ca + Mg) and Ce/Ce* of the Dengying Formation, South China. Issue 6 (9th August 2022) - Ding, Yi; Sun, Wei; Liu, Shugen; Xie, Jirong; Tang, Dongjie; Zhou, Xiqiang; Zhou, Limin; Li, Zhiwu; Song, Jinmin; Li, Zeqi; Xu, Hongyuan; Tang, Pan; et al.
Abstract: Most previous studies focused on the redox state of the deep water, leading to an incomplete understanding of the spatiotemporal evolution of the redox‐stratified ocean during the Ediacaran–Cambrian transition. In order to decode the redox condition of shallow marine environments during the late Ediacaran, this study presents I/(Ca + Mg), carbon and oxygen isotope, major, trace, and rare earth element data of subtidal to peritidal dolomite from the Dengying Formation at Yangba, South China. In combination with the reported radiometric and biostratigraphic data, the Dengying Formation and coeval successions worldwide are subdivided into a positive δ 13 C excursion (up to ~6‰) in the lower part (~551–547 Ma) and a stable δ 13 C plateau (generally between 0‰ and 3‰) in the middle‐upper part (~547–541 Ma). The overall low I/(Ca + Mg) ratios (<0.5 μmol/mol) and slightly negative to no Ce anomalies (0.80 < [Ce/Ce*]SN  < 1.25), point to low‐oxygen levels in shallow marine environments at Yangba. Moreover, four pulsed negative excursions in (Ce/Ce*)SN (between 0.62 and 0.8) and the associated two positive excursions in I/(Ca + Mg) ratios (up to 2.02 μmol/mol) are observed, indicative of weak oxygenations in the shallow marine environments. The comparison with other upper Ediacaran shallow water successions worldwide reveals that the (Ce/Ce*)SN and I/(Ca + Mg) values generally fall in the Precambrian range but their temporal trends differ among these successions (e.g., Ce anomaly profiles significantly different between Yangba and the Yangtze Gorge sections), which point to low oxygen levels with high redox heterogeneity in the surface ocean. This is consistent with the widespread anoxia as revealed by low δ 238 U values reported by previous studies. Thus, the atmospheric oxygen concentrations during the late Ediacaran are estimated to be very low, similar to the case during the most Mesoproterozoic to early Neoproterozoic period.